A review of Helicobacter pyloridiagnosis, treatment, and methods to detect eradication - Garza González, Elvira; Perez Perez, Guillermo Ignacio; Maldonado Garza, Héctor Jesús; Bosques Padilla, Francisco Javier (WJG Press, 2014)
Helicobacter pylori (H. pylori) affects nearly half of the world’s population and, thus, is one of the most frequent and persistent bacterial infections worldwide. H. pylori is associated with peptic ulcer disease, gastric ulcers, mucosa-associated lymphoid tissue lymphoma, and gastric cancer. Various diagnostic methods exist to detect infection, and the choice of one method or another depends on several factors, such as accessibility, advantages and disadvantages of each method, cost, and the age of patients. Once H. pylori infection is diagnosed, the clinician decides whether treatment is necessity, according to the patient’s clinical condition. Typically, eradication of H. pylori is recommended for treatment and prevention of the infection. Cure rates with the standard triple therapy are acceptable, and effective quadruple therapies, sequential therapies, and concomitant therapies have been introduced as key malternatives to treat H. pylori infection. In this work, we review the main diagnostic methods used to identify H. pylori infection and to confirm eradication of infection. In addition, key factors related to treatment are reviewed.